2021
DOI: 10.3389/fgene.2021.666306
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Diagnostic Value of miR-497 and miR-1246 in Hepatocellular Carcinoma

Abstract: ObjectiveSerum microRNAs (miRNAs) may serve as biomarkers in various cancers. Our study aims to explore the roles of miR-497 and miR-1246 in hepatocellular carcinoma (HCC).MethodsThe expression levels of miR-497 and miR-1246 were measured by RT-PCR. A correlation analysis was conducted between the expression levels of miR-497 and miR-1246 and clinicopathological characteristics of patients. The receiver operating characteristic (ROC) curve was applied to evaluate the diagnostic efficacy in HCC. In addition, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…In particular, its upregulation has been associated with tumor growth, metastasis, and drug resistance in different types of cancer. 72 , 73 , 74 In breast cancer, exosomal miR-1246 has been used as diagnostic biomarker because of its high expression specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its upregulation has been associated with tumor growth, metastasis, and drug resistance in different types of cancer. 72 , 73 , 74 In breast cancer, exosomal miR-1246 has been used as diagnostic biomarker because of its high expression specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exome sequencing identified SUCO mutations in mesial temporal lobe epilepsy, and a lack of SUCO led to abnormal development of neurons ( Sha et al, 2015 ). SUCO was found to be upregulated in hepatocellular carcinoma ( Yue et al, 2019 ) and may be targeted by miR-497 ( Chen et al, 2021 ). Our data showed that circ_0000160 was downregulated, while the host gene SUCO showed no significant change in breast cancer with lymph node metastasis compared with those without lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of many microRNAs were closely associated with the degree of differentiation, and tumor metastasis of HCC, such as miR-497, miR-1246, and miR-378a-3p ( 135 , 136 ). In addition, miR-378a-3p was also proved to directly regulate PD-L1 and STAT3 signaling to inhibit HCC, which may be a potential target in the future ( 137 ).…”
Section: Epigenetic Modification-related Mechanisms Of Hcc Resistance...mentioning
confidence: 99%